KOALISI DOMINAN HUMAS DPR-RI SEBAGAI BOUNDARY SPANNER DALAM MEWUJUDKAN GOOD GOVERNANCE MELALUI INFORMASI PUBLIK - Kurniawan Prasetyo (Universitas Mercu Buana, 2016)
Abstract: This study aims to determine the role of public relations of DPR RI in the dominant coalition asboundary spanner for achieving good governance through public information. As the cornerstone of this study,researcher used the concept of the dominant coalition by James E. Grunig. The ability of a public relations thatcan be accepted by the dominant coalition in an organization cannot be separated from the role and function isas a strategic decision maker, boundary spanner, and strategic management. This study uses a constructivistparadigm with the case study method. The data collection is done by in-depth interviews. Based on the results ofresearch and data analysis, it could be concluded that the Public Relations of DPR RI does not belong to thedominant coalition of organizations and do not represent the concepts used in this study. The role and functionof PR as boundary spanner in the dominant coalition lies on The News Parliament Bureau. In order to realizegood governance through public information, the dominant coalition public relations lie on The NewsParliament Bureau with integration between public relations and other work units within the scope of internalBureau. Public Relations in DPR RI only a labeling, but the real public relations functions carried by The NewsParliament Bureau.Keywords: dominant coalition, public relations, governance